Ecohydraulics exemplifies the emerging "paradigm of the interdisciplines". Issue 1 (2nd July 2016) - Nestler, John M.; Stewardson, Michael J.; Gilvear, David J.; Webb, J. Angus; Smith, David L.
ABSTRACT: The basic premise underlying ecohydraulics is deceptively simple: create a new discipline focused on the effects of water movement in aquatic ecosystems by melding principles of aquatic ecology (including aspects of fluvial geomorphology) and engineering hydraulics. However, advancing ecohydraulics as a synthetic, organized field of study is challenging because hydraulic engineers and ecologists (1) study processes that differ substantially in spatial and/or temporal scale; (2) have very different approaches to modelling; (3) utilize different sets of mathematical formulations, concepts, and assumptions; and (4) address problems with vastly different patterns of complexity and uncertainty. The differences between engineering and ecology must be reconciled within a set of concepts and practices applicable to ecohydraulics. This reconciliation is essential if ecohydraulics is to achieve the scientific esteem of its parent disciplines. First, we review how the competing paradigms of determinism and empiricism structure engineering and ecology, respectively. We then derive two guiding principles that facilitate the integration of ecology and hydraulics, the single reference framework and the multiple reference framework guiding principles. Third, we provide illustrative examples of these principles using a simple hydraulic fish habitat analysis based on physical habitat simulation (PHABSIM) system of the instream flow incremental methodology (IFIM) and a detailed fish movement model using Eulerian–Lagrangian–Agent methods (ELAMs). Based on these examples, we develop insights and conclusions to guide further advances in ecohydraulics and, perhaps even serve as a template to aid development of other interdisciplinary fields.